Critical review of dark tourism: tourists’ perceptions and behaviour - Ramlee, Farah Hasyimah; Hussin, Siti Rahayu; Hashim, Haslinda (Global Academic Excellence, 2018)
There is a growing interest in dark tourism as evident in the increased number of publications discussing dark tourism, as well as the number of dark destinations and tourists visiting dark destinations all over the world. Past literature has concentrated on the designation and theoretical aspects of dark tourism. Emphasis was given on the scope of dark tourism, site typology, managerial aspects and issues in developing dark destinations. Thus, less is known on the travel behaviour to these places. In addition, the early studies on tourists’ behaviour to the dark destination are majorly speculated. Among the most frequently cited factors influencing travel behaviour are tourists’ motivation and experience, emotions, and perceptions towards dark tourism. Therefore, this paper will critically review the definitions of dark tourism, tourist motivation to visit dark destinations and other travel behaviours on dark tourism.